Caracterización de ciclodipéptidos con actividad biológica procedentes de aislados bacterianos originarios de pozas de Cuatro Ciénegas, Coahuila - Martínez Carranza, Enrique (Universidad Michoacana de San Nicolás de Hidalgo, 2015)
The Cuatro Cienegas basin in Mexico has been described as an important biodiversity reservoir within the Chihuahuan desert. Most of the aquatic habitats are not permanent. Between locations, environmental conditions can vary in water chemistry, flow rate and the volume of spring discharge. Moreover, most aquatic habitats in this area are extremely oligotrophic due to the almost negligible phosphorous levels. While some studies have sought to describe and characterize the diversity of prokaryotes in the basin, little has been to understand and interpret how the populations are related, if exist communication between them, through which molecular mechanisms performed competition for nutrients, or mechanisms used to control microbial populations. Thus, the study of the mechanisms that bacteria use to compete by resources in this environment has ecological and evolutionary interest and could lead to relevant biotechnological discoveries. On the other hand, cyclic dipeptides (CDPs) also known as 2, 5-diketopiperazines (DKPs) are relatively simple compounds. The ability of microorganisms to produce diketopiperazines is widespread and published data have shown that about 90% of Gram-negative bacteria produce them. Diketopiperazines have also isolated from Gram-positive bacteria, fungi and higher marine organisms. Biosynthesis of CDPs can be achieved by dedicated nonribosomal peptide synthetases (NRPS). Recently was discovered a new biosynthetic route involving a named cyclodipepdide synthases. Important biological activities of diketopiperazines are as antibacterial, antifungal, antitumour, antiviral. In addition recently, was described that diketopiperazines are able to activate or antagonize LuxR-mediated quorum-sensing systems of bacteria, and they are considered to influence cell-cell signaling. In our work we evaluated the production and biological activity of CDPs of bacterial isolates originating in pools of Cuatro Cienegas, Coahuila with the purpose of know if these molecules have influence in the control of bacterial populations. First we did competition assays and select those isolates with ability to inhibit the growth of other isolates, the selected isolates extractions were made with ethyl acetate and then analyzed by HPLC, a comparative analysis was made and then analyzed by GC-MS to identify the compounds. The ability of the extracts to inhibit the growth of other isolates was tested, and compared with the data obtained from the analysis by HPLC and GC-MS. The presence of CDPs cycle (Pro-Val) and cycle (Pro-Leu) was observed, and also an antibiotic previously reported called 2, 4-diacetylphloroglucinol (2, 4-DAPG).

La cuenca de Cuatro Ciénegas en el desierto de Chihuahua en México, ha sido descrita como un reservorio importante de biodiversidad. La mayoría de los hábitats acuáticos son extremadamente oligotróficos debido entre otros factores a la deficiencia de fósforo. Pocos son los estudios que han intentado describir y caracterizar la diversidad de las poblaciones bacterianas en la cuenca, por lo que se conoce poco acerca de la relación de competencia entre dichas poblaciones. Por otro lado, los ciclodipéptidos (CDPs) y sus derivados, las dicetopiperazinas (DKPs) son componentes relativamente simples, constituidos por dos aminoácidos unidos mediante dos enlaces peptídicos. La síntesis de los CDPs está ampliamente distribuida en bacterias, hongos y organismos superiores, encontrado importantes actividades biológicas asociadas a éstos; entre las cuales se han descrito propiedades antimicrobianas, antifúngicas, antivirales y anticancerígenas. Recientemente se ha descrito que las DKPs son capaces de activar y/o antagonizar la percepción de quórum bacteriano mediada por reguladores transcripcionales del tipo LuxR. En el presente trabajo evaluamos la producción y actividad biológica de los CDPs procedentes de aislados bacterianos originarios de Cuatro Ciénegas, con el propósito de determinar si éstos compuestos influyen en el control poblacional bacteriano. La totalidad de los aislados estudiados pertenecieron a la división Gamaproteobacteria se confrontaron mediante ensayos de competencia para evaluar su capacidad de inhibir el crecimiento bacteriano. Mediante este escrutinio se seleccionaron 16 aislados capaces de producir inhibición del crecimiento a otros aislados, a los cuales les fue analizado el perfil de síntesis de CDPs extraídos de los cultivos bacterianos usando extracciones líquido-líquido con solventes mediante HPLC y CG-EM. Se confirmó la presencia de los CDPs ciclo (Pro-Val) y ciclo (Pro-Leu) en la mayoría de los extractos analizados, además del antibiótico 2,4-diacetil-fluoroglucinol (DAPG).
Instituto de Investigaciones Químico Biológicas. Maestría en Ciencias en Biología Experimental
Keywords: info:eu-repo/classification/cti/6; IIQB-M-2015-0243; Ciclodipéptidos; Cuatro Ciénegas; Ciclo(Pro-Val); http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3913